A hybrid grey wolf assisted-sparrow search algorithm for frequency control of RE integrated system - Fadheel, Bashar Abbas; Wahab, Noor Izzri Abdul; Mahdi, Ali Jafer; Premkumar, Manoharan; Radzi, Mohd Amran Bin Mohd; Soh, Azura Binti Che; Veerasamy, Veerapandiyan; Irudayaraj, Andrew Xavier Raj (Multidisciplinary Digital Publishing Institute, 2023)
Nowadays, renewable energy (RE) sources are heavily integrated into the power system due to the deregulation of the energy market, environmental and economic benefits. The intermittent nature of RE and the stochastic behavior of loads creates frequency aberrations in interconnected hybrid power systems (HPS). Hence, this paper attempts to develop an optimization technique to tune the controller optimally to regulate the frequency. A hybrid Sparrow Search Algorithm-Grey Wolf Optimizer (SSAGWO) is proposed to optimize the gain values of the proportional integral deriva-tive controller. The proposed algorithm helps to improve the original versions' exploration and exploitation. The optimization technique is coded in MATLAB and applied for frequency regula-tion of two-area HPS developed in Simulink. The efficacy of the proffered hybrid SSAGWO is first assessed on standard benchmark functions and then applied to the frequency control of the HPS model. The results obtained from the multi-area multi-source HPS demonstrate that the proposed hybrid SSAGWO optimized PID controller performs significantly by 53, 60, 20, and 70 in terms of settling time, peak undershoot, control effort, and steady-state error values than other state-of-the-art presented in the literature. Moreover, the robustness of the proffered method is also evaluated under the random varying load, variation of HPS system parameter, and weather intermittency of RE resources in real-time conditions. Furthermore, the controller's efficacy was also demonstrated by performing a sensitivity analysis of the proposed system with variations of 75 and 125 in the inertia constant and system loading from the nominal values. The results show that the proposed technique damped out the transient oscillations with minimum settling time. Moreover, the stability of the system is analyzed in the frequency domain using bode analy-sis.